New records of the genus Pachygrapsus (Crustacea: Decapoda) from the central Mediterranean Sea with a review of its Mediterranean zoogeography - CROCETTA, F.; MIFSUD, S.; PAOLINI, P.; PISCOPO, J.; SCHEMBRI, P.J. (Mediterranean Marine Science, 2011)
The occurrence of Pachygrapsus maurus and Pachygrapsus transversus is reported from the Maltese Islands for the first time on the basis of one specimen of P. maurus collected in 1990 and numerous recent specimens, and the distribution of the two species is mapped. The controversial presence of P. maurus in Italy is confirmed and two new sites for this species are reported, including the first for the mainland of Italy. The examination of the historical specimen of P. maurus from the Genova area revealed a misidentification of P. transversus; this record could be a result of ship-mediated transport. First notes on the habitat of P. maurus in the central Mediterranean Sea are given. Updated maps of the distribution of P. maurus and P. transversus in the Mediterranean are provided and the zoogeography of these species is revisited.